Determinants of Continuance Intention to Use Mobile Payments: A Meta-Analysis - K. A., Ashique Ali; Subramanian, Rameshkumar (Indian Journal of Marketing, 2024)
Purpose : This study aimed to consolidate the major determinants of continuance intention to use mobile payments by employing meta-analysis. Design/Methodology/Approach : The application of systematic inclusion/exclusion criteria resulted in the retrieval of 54 journal articles relating to the subject chosen for this study. An in-depth literature analysis helped identify the various antecedents of continuance intention to use mobile payments. A weighted analysis followed by a meta-analysis based on 193 bivariate correlations paved the way for developing the mobile payment continuance intention model (MPCIM). Meta Essentials 1.5 was used for analysis. Findings : The primary predictor of continuing to intend to use mobile payments is satisfaction, which is followed by expectation of effort and expectation of performance. Perceived behavioral control was found to have the least consolidated effect on the desire to continue using mobile payments; whereas, perceived risk had no significant combined effect. Practical Implications : The impact of the primary factors of continued desire to use mobile payments will be consolidated and presented to regulatory bodies, service providers, and other interested parties. Originality/Value : We have made an effort to close this gap by doing a meta-analysis of the primary factors that determine whether or not a person would continue to want to utilize mobile payments.